2013
DOI: 10.1128/iai.00688-13
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive Property within the Streptococcus pneumoniae Cell Wall That Inhibits Generation of T Follicular Helper, Germinal Center, and Plasma Cell Response to a Coimmunized Heterologous Protein

Abstract: We previously demonstrated that intact, inactivated Streptococcus pneumoniae (unencapsulated strain R36A) inhibits IgG responses to a number of coimmunized soluble antigens (Ags). In this study, we investigated the mechanism of this inhibition and whether other extracellular bacteria exhibited similar effects. No inhibition was observed if R36A was given 24 h before or after immunization with soluble chicken ovalbumin (cOVA), indicating that R36A acts transiently during the initiation of the immune response. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Moreover, it has previously been demonstrated that S. pneumoniae inhibits IgG responses to a number of co-immunized soluble antigens. More precisely, S. pneumoniae was found to mediate a significant reduction in the formation of Ag-specific splenic T follicular helper and germinal center B cells and antibody-secreting cells in the spleen and bone marrow in response to OVA32. Similarly, in a lethal coinfection model of influenza virus and S. pneumoniae , coinfection caused depletion of CD4 + T cells and B cells in mediastinal lymph nodes and spleen, with concomitant reduction in virus-specific antibody responses33.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, it has previously been demonstrated that S. pneumoniae inhibits IgG responses to a number of co-immunized soluble antigens. More precisely, S. pneumoniae was found to mediate a significant reduction in the formation of Ag-specific splenic T follicular helper and germinal center B cells and antibody-secreting cells in the spleen and bone marrow in response to OVA32. Similarly, in a lethal coinfection model of influenza virus and S. pneumoniae , coinfection caused depletion of CD4 + T cells and B cells in mediastinal lymph nodes and spleen, with concomitant reduction in virus-specific antibody responses33.…”
Section: Discussionmentioning
confidence: 96%
“…We observed that Pn strongly suppressed the IgG response to co-immunized, heteroglogous proteins, including chicken ovalbumin (cOVA) (15, 16). Specifically, the inhibition of induction of serum cOVA-specific IgG, in response to i.v.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the inhibition of induction of serum cOVA-specific IgG, in response to i.v. administered cOVA was associated with a marked reduction in the generation of specific CD4+ GC T follicular helper cells (Tfh) and GC B cells in the spleen, and antibody-secreting cells (ASC) in spleen and bone marrow, with no change in the percentages of T regulatory cells and only modest changes in early T cell proliferation (16). We further demonstrated that this inhibitory property was contained within the Pn cell wall.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The process was carried out as described earlier (33). Briefly, RBC-lysed spleen cells from DO11.10 mice (2.5 3 10 7 cells) were incubated in 1 ml 5 mM CFSE (Vybrant CFDA SE; Molecular Probes) in PBS for 10 min at 37˚C.…”
Section: Measurement Of T Cell Proliferation By Cfse Dilutionmentioning
confidence: 99%